MODE OF CONDUCTING AN AUDIT. - Staub, Walter A. (The Accounting Review, 1943)
Periodical examinations of the accounts of commercial and financial institutions, special examinations for prospective investors, investigations on behalf of creditors and trustees in bankruptcy, examinations to ascertain the cause of decreasing profits, exhaustive audits preparatory to installing improved systems of financial and cost accounts, and investigations of the accounts of public officials at the be best of dissatisfied citizens are but a few of the many purposes which clients have in mind when desiring to have the accounts of an undertaking audited. The object of the auditor should be, in the main, three folded. They are detection of fraud, discovery of errors of principle, verification of the mechanical accuracy of accounts. As has been pointed out by other writers, the attempted concealment of fraud must be accomplished by commission of either an error of principle or one in the mechanical work of the accounts; owing, however, to its importance and often its predominating importance, the detection of fraud is conceded a separate place among the objects of an audit.